Metal recovery from copper converter slag by roasting with ferric sulphate - Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 1997)
A study of the recovery of copper, cobalt, nickel and zinc from copper converter slag by roasting with ferric sulphate is reported. Roasting of converter slag with ferric sulphate, followed by leaching with water, was carried out in order to bring the metal values into solution. For 500°C roasting temperature, 120 min roasting time and Fe2(SO4)3 · xH2O/slag = 1 ratio, recoveries of copper, cobalt, nickel and zinc were about 93%; 38%; 13% and 59%, respectively. Higher extraction yields could be achieved with a higher ratio of Fe2(SO4)3 · xH2O/slag for copper and zinc, whereas cobalt and nickel could not be extracted in acceptable yields. Using H2SO4 in the leaching process markedly improves the metal recoveries.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ferric sulfate; Metal recovery; converter slag; sulfation roasting